THE INFLUENCE OF JOB SATISFACTION ON EMPLOYEE PERFORMANCE - Djuli, Fatma Azhara; Abdussamad, Zuchri; Sulila, Ismet (Public Policy Journal, 2023)
This study aims to determine the effect of job satisfaction on employee performance at the Gorontalo City Pamong Praja Police Unit. The research approach used in this research is quantitative, where the sample in this study amounted to 62 employees using a research approach and research design. The data collection technique was carried out by distributing questionnaires to employees. The data analysis technique used is simple regression analysis. The results of the regression analysis test show the effect of job satisfaction on employee performance at the Gorontalo City Pamong Praja Police Unit. Thus the first hypothesis (H1) can be proven or accepted. The R Square value is 0.419 in other words 41.9% of the independent variable, namely (X) Job Satisfaction, contributes to the variable (Y) Employee Performance, while the remaining 58.1% is in the form of contributions from other variables not examined in this study, namely organizational culture, work motivation, and work discipline